Prove that 2cot2x+tanx=cotx

2cot2x= 2(1/tan2x)= 2(1/(2tanx/1-tan2x))=2(1-tan2x)/2tanx= (1-tan2x)/tanx(1-tan2x)/tanx +tanx=(1-tan2x)/tanx +tan2x/tanx=1/tanx=cotx

Answered by Alisa D. Maths tutor

19054 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Show how you can rewrite (x+1)(x-2)(x+3) into the form of ax^3 + bx^2 + cx + d


How exactly does integration by parts work?


Let f(x) = 5x^4 + 6x^3 + 3, find dy/dx at x = 3


Integrate sin^2(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences